An Extremely Rare Complication of Varicose Vein Surgery: Retained Foreign Body - Orhan Fındık; Ufuk Aydın; Çağrı Düzyol; Özgür Barış; Cevdet Uğur Koçoğulları (Case Reports in Surgery)
Foreign body is among complications of surgery. But as a complication of varicose vein surgery it was reported extremely rarely and, to our knowledge, there is only one paper in the literature. A case with retained sponge which was detected five months after varicose vein surgery was presented.